Problemy pojęciowe i systemowe decentralizacji terenowej w ujęciu planistyczno - finansowym - Denek, Emilia (Wydział Prawa i Administracji UAM, 1982)
The system of administration of local economy has been frequently reformed troughout the past 25 years in order to decentralize it. That decentralization proved to be ambiguous both in the practice and literature. In any case the aim of limiting decisions of regional organs with their incomes was followed. It is not possible in practice to replace the centralized system of local economy administration with the decentralized one. It is only possible to introduce the mixed system combining elements of the centralized and decentralized systems. Aiming at decentralization is therefore manifested with limiting directive methods of administration and expanding the parametric method of management within the framework of the mixed system. The authoress discusses the role of planning and financial instruments in various systems of administration, focusing on sources and fournis of budgetary incomes of the regional organs in the aspect of their utilization as parametric instruments of economy management in those areas.
Conceptual analysis of regionally decentralized systems in terms of planning and finances